Media and Brazilian paralympic movement: relationships under Brazilian Paralympic Commitee manager's perception - Marques, Renato Francisco Rodrigues; Gutierrez, Gustavo Luis; Almeida, Marco Antonio Bettine de; Menezes, Rafael Pombo (Brazilian journal of physical education and sport, 2013)
The goal of this study was to investigate the relationship between media and disclosure and commercialization of Brazilian Paralympic Movement. The research methodology was based on: semistructured interviews with managers of the Brazilian Paralympic Committee about management processes of the paralympic movement and relationship with the media; Data from interviews were analyzed using the Discourse Collective Subject method and reflections based on Pierre Bourdieu's categories. RESULTS: the exploitation of the paralympic movement by the Brazilian media is something that can be improved; Paralympic sport does not have a symbolic capital that legitimizes commercially, although it has developed in this regard; To reach better commercial relevance, it may be interesting that the Paralympic movement continues its search process by increasing professionalization and fits the directions proposed by the media. Due to such approach, the exposure of your slope high performance sport might be improved, showing its ability to create idols, produce pleasurable emotions and attract interest of consumers.